Personalised A.I. chatbot for Kampar tourism mobile application - Low, Zhi Yuan (2021)
In this modern and digitalized era, Artificial Intelligence (AI) has become popular in almost all sectors. One of the most common applications of AI is chatbot. In the market today, there are lots of chatbots applications available, such as Amazon’s Alexa, Apple’s Siri and Google’s Google Assistant. Most of the businesses have implemented chatbots due to its high availability and efficiency, especially for customer service purpose. However, most of the chatbots are rule-based. The chatbots will return the respective results to the users only if the predefined questions are asked. Everyone gets the same answer for similar inputs. For general Question and Answer (QnA), rule-based chatbots are more than enough. Yet, for the tourism sector, chatbots which can learn the users’ preferences and recommend them with their interested things are more likely to satisfy the users. Different tourists may have different personalities, and thus feel interested in different tourist attractions. If they manage to get the recommendations which match their needs, the user experience will be better. To solve the problem stated above, an enhanced version of KamparBot, which is also one of the features of GoKampar travel guide application is proposed. The previous version of KamparBot allows the users to search for restaurant, lodging and tourist attractions when travelling in Kampar. Compared with the original application, the new KamparBot will be able to collect users’ favourites and personalities for personalising their recommendations, instead of just showing same responses to all users who ask similar questions. Hence, this project will focus on developing an AI-based chatbot which can understand the user’s needs and preferences and therefore recommend suitable places based on machine learning techniques.